Body Mass Index and Early Kidney Function Decline in Young Adults: A Longitudinal Analysis of the CARDIA (Coronary Artery Risk Development in Young Adults) Study - Grubbs, Vanessa (2013)
BACKGROUND: Identifying potentially modifiable risk factors is critically important for reducing the burden of chronic kidney disease. We sought to examine the association of body mass index (BMI) with kidney function decline in a cohort of young adults with preserved glomerular filtration at baseline. STUDY DESIGN: Longitudinal cohort. SETTING & PARTICIPANTS: 2,891 black and white young adults with cystatin C-based estimated glomerular filtration rate (eGFR(cys)) >90 ml/min/1.73 m(2) taking part in the year-10 examination (in 1995–1996) of the Coronary Artery Risk Development in Young Adults (CARDIA) Study. PREDICTOR: BMI, categorized as 18.5–24.9 (reference), 25.0–29.9. 30.0–39.9, and ≥40.0 kg/m(2). OUTCOMES: Trajectory of kidney function decline, rapid decline (>3% per year), and incident eGFR(cys) <60 ml/min/1.73 m(2) over 10 years of follow-up. MEASUREMENTS: GFR(cys) estimated from the CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) equation for calibrated cystatin C at CARDIA years 10, 15, and 20. RESULTS: At year 10, participants had a mean age of 35.1 years, median eGFR(cys) of 114 ml/min/1.73 m(2), and 24.5% had BMI ≥30.0 kg/m(2). After age 30 years, average eGFR(cys) was progressively lower with each increment of BMI after adjustment for baseline age, race, sex, hyperlipidemia, smoking status, and physical activity. Higher BMI category was associated with successively higher odds of rapid decline (for 25.0–29.9, 30.0–39.9, and ≥40.0 kg/m(2), the adjusted ORs were 1.50 [95% CI, 1.21–1.87], 2.01 [95% CI, 1.57–2.87], and 2.57 [95% CI, 1.67–3.94], respectively). Eighteen participants (0.6%) had incident eGFR(cys) <60 ml/min/1.73 m(2). In unadjusted analysis, higher BMI category was associated with incident eGFR(cys) <60 ml/min/1.73 m(2) (for 25.0–29.9, 30.0–39.9, and ≥40.0 kg/m(2), the ORs were 5.17 [95% CI, 1.10–25.38], 7.44 [95% CI, 1.54–35.95], and 5.55 [95% CI, 0.50–61.81], respectively); adjusted associations were no longer significant. LIMITATIONS: Inability to describe kidney function before differences by BMI category were already evident. Absence of data on measured GFR or GFR estimated from serum creatinine. CONCLUSIONS: Higher BMI categories are associated with greater declines in kidney function among a cohort of young adults with preserved GFR at baseline. Clinicians should vigilantly monitor overweight and obese patients for evidence of early kidney function decline.